Patient trust in nurses: exploring the relationship with care quality and communication skills in emergency departments - Zahra Bahari; Nazila Vosoghi; Nargess Ramazanzadeh; Shohreh Moshfeghi; Masoumeh Aghamohammadi (BMC, 2024)
Abstract Background Patient trust in medical staff is an important ethical issue that can influence various patient behaviors and attitudes, such as seeking healthcare, sharing confidential information, accepting treatment, and adhering to recommendations. This study aimed to assess patient trust in nurses and its relationship to the quality of care and communication skills of nurses in emergency departments. Methods This descriptive correlational study was conducted in 2023 in the emergency departments of medical training centers of Ardabil University of Medical Sciences, Iran. A total of 378 patients was selected using a quota sampling method. Data were collected using three valid and reliable tools: the Quality Patient Care (QUALPAC) scale, the Health Communication Feedback Questionnaire (HCFQ), and the Trust in Nurses Scale (TNS).The data were analyzed using independent t-tests, one-way analysis of variance, and Pearson's correlation coefficient tests using SPSS version 24. Results The majority of patients (99.2%) rated nurses' communication skills as moderate, with none rating them as poor. The average scores were 27.59 ± 2.76 for patient trust in nurses, 72.43 ± 3.30 for nurses' communication skills, and 198.30 ± 14.60 for the quality of nursing care. A significant correlation was found between patient trust in nurses and the overall quality of nursing care (r = 0.256, P < 0.001) as well as its dimensions. However, there was no significant relationship between patient trust in nurses and patient's perception of the nurses' communication skills (r = 0.046, P = 0.369). Conclusions The findings indicate that patient trust in nurses is positively and significantly associated with the perceived quality of nursing care. As the quality of care improves, patient trust in nurses also increases. Therefore, nurses should focus on providing high-quality care to enhance patient trust.